Relationship between Training and Internal Staffing with Employee Work Performance (A Study at the Public Works Department of Sukabumi Regency) - Budi Rismayadi; Mumun Maemunah; Citra Savitri (International Journal of Science and Society, 2019)
The purpose of this study was to determine the relationship of training in improving employee performance and internal staffing relationships in improving employee performance and how the relationship of training and internal staffing in improving employee performance. The research method used is a verification method of research with multiple linear regression models, processing data using multiple correlation analysis and using the F test and t test. The total population taken was 58 permanent employees and a random sample of 50 respondents and the data collection technique used a questionnaire with a Likert scale. From the calculation of the multiple correlation coefficient between training and employee performance resulted in a positive number of 0.98 which means that employee performance is greatly influenced by training. This shows the relationship of training with employee performance is very strong. These results are supported by significant test results t (t arithmetic = 1.36> = 1.30). This means that training makes a meaningful contribution; while internal staffing (tcount = 0.009 <ttable = 1.30) showed less significant relationship in improving employee work performance, even though it had a correlation coefficient (ry2 = 0.98). Training and internal staffing on employee performance have a very strong relationship as evidenced by a variance of 96.52%. and the remaining 3.48% is caused by other factors.